Atomic force microscopy study of cellulose surface interaction controlled by cellulose binding domains - Nigmatullin, R. (2004)
Colloidal probe microscopy has been used to study the interaction between model cellulose surfaces and the role of cellulose binding domain (CBD), peptides specifically binding to cellulose, in interfacial interaction of cellulose surfaces modified with CBDs. The interaction between pure cellulose surfaces in aqueous electrolyte solution is dominated by double layer repulsive forces with the range and magnitude of the net force dependent on electrolyte concentration. AFM imaging reveals agglomeration of CBD adsorbed on cellulose surface. Despite an increase in surface charge owing to CBD binding to cellulose surface, force profiles are less repulsive for interactions involving, at least, one modified surface. Such changes are attributed to irregularity of the topography of protein surface and non-uniform distribution of surface charges on the surface of modified cellulose. Binding double CBD hybrid protein to cellulose surfaces causes adhesive forces at retraction, whereas separation curves obtained with cellulose modified with single CBD show small adhesion only at high ionic strength. This is possibly caused by the formation of the cross-links between cellulose surfaces in the case of double CBD.